“NEW WOMAN” IN THE MODERN KOREAN NOVEL "VEGETARIAN" BY HAN KANG - Soleeva Aziza Mukhamadievna (Research Focus International Scientific Journal, 2025)
The article examines the position of a woman and her role in society. Society has changed throughout Korean history and contradictions continue to this day. The “New Woman” movement influenced women’s lives and also made adjustments to the role of men, which led to a significant revolution in society and the expansion of the concept of “gender role” in Korea. Under the influence of time, the concept of the “New Woman” acquired new features in the novel “The Vegetarian” by the modern Korean writer Han Gang.